PREVALENCE OF INSULIN-TREATED TYPE 2 DIABETES MELLITUS IN NORTHERN JORDAN: LIFE STYLE, FAMILIAL INHERITANCE AND MATERNAL INFLUENCE - Irshaid, Fawzi (European Scientific Journal, ESJ, 2014)
Background and Aims: Type 2 Diabetes mellitus (T2D) is a chronicprogressive metabolic disorder characterized by hyperglycemia and oftenassociated with several etiologies. The prevalence of T2D and its associatedrisk factors among adults residing in Al-Mafraq district-Jordan are notdocumented, particularly for T2D patients who were treated with insulintherapy. Thus, the aims of this study were to estimate the change in theprevalence of T2D among adults living in this district from 2000 to 2011 andinvestigate its associated risk factors with emphasis on genetic factors.Methods: Data for T2D patients taking insulin were obtained retrospectivelyfrom the primary health center of Al-Mafraq for the years of 2000 to 2011.The prevalence of T2D among adults was calculated as the number of casesper 100,000 persons. Structured questionnaires were prepared for collectingsociodemographic and clinical data from random sample of 206 patients withT2D on insulin therapy. Data were collected between the period of 2010 and2011. Patients were between 17 to 83 years old, with a mean age of 51.7 ±14.6 (±SD). Also, 196 healthy adults with match age and gender wereincluded in this study.Results: The prevalence of T2D increased from 116 per 100,000 individualsin 2000 to 223 per 100,000 individuals in 2011 in this district (an increase of92%). About 73% of these patients had at least one diabetic family member,this rate was significantly higher than that for controls (10.7%) (P < 0.01).About 50% of the patients had a diabetic mother compared with 12.6% whohad a diabetic father (P < 0.01), suggesting maternal influence. Data alsorevealed that sedentary life style and overweight/obesity and age (40 yearsand above) were significantly associated with incidence of T2D. In contrast,gender, employment status and education levels did not affect the prevalenceof T2D (P > 0.05). Conclusion: In this district, a significant increase in the prevalence ofinsulin-treated T2D was documented over 12 years in both sexes. Familialinheritance, maternal influence, sedentary life style and overweight/obesityas well as the interaction between them appear to be responsible for suchhigh increase in the risk of T2D.